2020
DOI: 10.1177/2397198320904178
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcome measures in systemic sclerosis–related interstitial lung disease for clinical practice and clinical trials

Abstract: Systemic sclerosis (SSc) is a progressive vasculopathic, fibrosing autoimmune condition, portending significant mortality; wherein interstitial lung disease (ILD) is the leading cause of death. Although lacking a definitive cure, therapeutics for (SSc-ILD) that stave progression exist with further promising primary and adjuvant compounds in development, as well as interventions to reduce symptom burden and increase quality of life. To date, there has been a significant but varied history related to systemic sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…Clearly, there is a need for guidance in the new treatment regimens, in particular regarding the use of upfront or add-on combination treatment with immunosuppressants/antifibrotic, which could be the possible second/third level option in case of treatment failure. Hopefully, our understanding of the pathogenesis of SSc-ILD will evolve, along with the development of specific therapies for the organ systems affected by this disease, thus improving patients' survival, function, and quality of life [92,93]. Funding: The authors received no financial support for the research, authorship, and/or publication of this article.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, there is a need for guidance in the new treatment regimens, in particular regarding the use of upfront or add-on combination treatment with immunosuppressants/antifibrotic, which could be the possible second/third level option in case of treatment failure. Hopefully, our understanding of the pathogenesis of SSc-ILD will evolve, along with the development of specific therapies for the organ systems affected by this disease, thus improving patients' survival, function, and quality of life [92,93]. Funding: The authors received no financial support for the research, authorship, and/or publication of this article.…”
Section: Discussionmentioning
confidence: 99%
“…Value-based health care, patient-reported outcomes (PRO) and treatment satisfaction are core values for new reference standards and quality metrics in patient management and drug approval by regulatory agencies (39,40). The creation of a new assessment tool for a complex rheumatological disease, like lcSSc, requires the incorporation of the patients' perspective, especially for the identification of the most important domains for this CRI.…”
Section: Challenges Ahead For a Combined Index Dedicated To Lcsscmentioning
confidence: 99%
“…Value-based healthcare, patient-reported outcomes (PROs), and treatment satisfaction are core values for new reference standards and therefore quality metrics in patient management and drug approval by regulatory agencies. 50,51 The creation of a new assessment tool for a complex rheumatological disease, like lcSSc, requires the incorporation of the patients’ perspective, especially for the identification of the most important domains for this combined response index. Comprehensive identification of outcome measures, including PRO, will therefore require highlighting the most relevant items within the domains that are considered the most bothersome by patients with lcSSc.…”
Section: Unmet Needs For a Combined Index Dedicated To Lcssc: The Casmentioning
confidence: 99%
“…Studies have shown that cough, dyspnoea, changes in physical function and fatigue are the lung-related symptoms of most concern to patients with connective tissue disease (CTD)-associated ILD, including SSc [ 10 , 11 ]. Thus, PRO measures are usually assessed in randomised clinical trials in SSc-ILD as secondary endpoints [ 12 ].…”
Section: Introductionmentioning
confidence: 99%